1990
DOI: 10.1073/pnas.87.5.1777
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNA encoding the 80-kDa subunit protein of the human autoantigen Ku (p70/p80) recognized by autoantibodies from patients with scleroderma-polymyositis overlap syndrome.

Abstract: Anti-Ku (p70/p80) autoantibodies in patients with scleroderma-polymyositis overlap syndrome recognize a 70-kDa/80-kDa protein heterodimer which binds to terminal regions of double-stranded DNA. In the present study, we isolated full-length cDNAs that encode the 80-kDa Ku subunit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(81 citation statements)
references
References 21 publications
4
75
2
Order By: Relevance
“…Thus, we examined the cellular localization of the Ku70 and Ku80 proteins in HeLa-S3 cells using confocal laser scanning microscopy ( Figure 1A). Double staining using antibodies speci®c for the Ku70 and Ku80 subunits, respectively, resulted in uorescence mainly in the nucleoplasm of almost all the interphase cells screened, as reported in previous studies (Reeves, 1985;Yaneva et al, 1985;Mimori et al, 1990;Koike et al, 1998). However, in the course of our study, we found that the staining pattern of Ku80 did not completely coincide with that of Ku70 in some cells ( Figure 1A).…”
Section: Resultssupporting
confidence: 86%
“…Thus, we examined the cellular localization of the Ku70 and Ku80 proteins in HeLa-S3 cells using confocal laser scanning microscopy ( Figure 1A). Double staining using antibodies speci®c for the Ku70 and Ku80 subunits, respectively, resulted in uorescence mainly in the nucleoplasm of almost all the interphase cells screened, as reported in previous studies (Reeves, 1985;Yaneva et al, 1985;Mimori et al, 1990;Koike et al, 1998). However, in the course of our study, we found that the staining pattern of Ku80 did not completely coincide with that of Ku70 in some cells ( Figure 1A).…”
Section: Resultssupporting
confidence: 86%
“…The Ku proteins were originally identified as autoantigens, recognized by the sera of patients with autoimmune diseases such as systemic lupus erythematosus and scleroderma (41). The two Ku proteins, Ku70 and Ku80, have been well demonstrated to dimerize and function in repair of DNA double strand breaks, DNA telomere length maintenance, transcription regulation, and V(D)J recombination (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of Ku80 Deletion Mutants with Full-length Ku70 -A number of potential functional domains have been identified in Ku80 based on sequence homology (17)(18)(19)36). These include leucine zipper-like domains that could promote protein-protein interaction as well as clusters of basic amino acid domains that could be involved in DNA recognition.…”
Section: Table Imentioning
confidence: 99%